2019
DOI: 10.1002/psp.2295
|View full text |Cite
|
Sign up to set email alerts
|

Bringing city size in understanding the permanent settlement intention of rural–urban migrants in China

Abstract: China's recent hukou reform provides opportunities for rural-urban migrants to acquire formal citizenship and for the country's urbanisation to step into a fair and humanistic stage. However, the between-city variation in migrants' intention of hukou transfer and the heterogeneity of its influencing factors have rarely been examined.These research gaps make it impossible to the rationality and effectiveness of the localised hukou entry criteria formulated by city governments. In this paper, we addressed the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 53 publications
(81 reference statements)
3
47
0
Order By: Relevance
“…Besides, the degree and quantity of group activities among rural residents were lower than those of urban citizens because of the economic gap and the widespread existence of virtual social networks in cities [50], which may also be the reason why rural social capital was lower than that of urban areas. Moreover, because of the implementation of the Chinese urbanization promotion strategy, young people who used to live in the countryside now prefer to make a living in the city [51], resulting in a large number of older adults and children left behind in the countryside. In addition to having lower socioeconomic statuses than the urban older people, the rural older people, particularly the widowed, may also not get timely support from their families.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the degree and quantity of group activities among rural residents were lower than those of urban citizens because of the economic gap and the widespread existence of virtual social networks in cities [50], which may also be the reason why rural social capital was lower than that of urban areas. Moreover, because of the implementation of the Chinese urbanization promotion strategy, young people who used to live in the countryside now prefer to make a living in the city [51], resulting in a large number of older adults and children left behind in the countryside. In addition to having lower socioeconomic statuses than the urban older people, the rural older people, particularly the widowed, may also not get timely support from their families.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cities with good public services set strict criteria for local hukou registration. As a result of this, differences in welfare state entitlements between local and non-local hukou holders could become even more magnified [5,[20][21][22].…”
Section: The 2014 Hukou Reformmentioning
confidence: 99%
“…Liu, Deng and Song [22] studied migrants' settlement intentions in 282 Chinese cities, and found that regional differences and city characteristics had a significant impact on the settlement choices of migrants. Correspondingly, migrants with different socio-demographic and economic features prefer different cities as their migration destination [21,31]. Gu, Liu and Shen [20] present the fact that in large and wealthy cities, there are many migrants who want to convert their hukou into a local one but they cannot do so because of the strict hukou access policies.…”
Section: Permanent Settlement and Hukou Transfer Intentions Of Migrantsmentioning
confidence: 99%
See 2 more Smart Citations